Genetic diversity of rodent blastocystis sp. From peninsular Malaysia - Farah Haziqah, Meor Termizi; Mohd Zain, Siti Nursheena; Chandrawathani, Panchacharam; Premaalatha, B.; Mohd Khalid, Mohd Khairul Nizam; Arutchelvan, R.; Govind, Suresh Kumar (Malaysian Society of Parasitology and Tropical Medicine, 2018)
Rodents are ubiquitous zoonotic vectors for many human pathogens including Blastocystis sp. In this study, we examined the prevalence and subtypes of Blastocystis sp. in rodents captured from Peninsular Malaysia. A total of 293 rodents predominantly brown rat (Rattus norvegicus) (290 of 293, 99.0%) and house shrew (Suncus murinus) (3 of 293, 1.0 %), were captured in the vicinity of popular eateries in two cities (Kuala Lumpur and Ipoh) in Peninsular Malaysia. In vitro cultivation method showed presence of Blastocystis sp. in approximately half (133 of 290, 45.9%) of the brown rats tested. Among the 47 Blastocystis isolates subtyped using partial small subunit ribosomal RNA gene analysis, ST4 was the most abundant (43 of 47, 91.5%) followed by ST1 (2 of 47, 4.3%), ST5 (1 of 47, 2.1%) and ST7 (1 of 47, 2.1%). Our findings highlighted the importance of rodents as a source of Blastocystis sp. infection in Malaysia and showed the high prevalence of ST4 within the rodent population infected with Blastocystis sp.